Extensive Frontoparietal Abscess: Complication of Frontal Sinusitis (Pott’s Puffy Tumor) - Raquel Andrade Lauria; Fernando Laffitte Fernandes; Thiago Pires Brito; Pablo Soares Gomes Pereira; Carlos Takahiro Chone (Case Reports in Otolaryngology)
First described in 1768, the Pott’s puffy tumor is a subperiosteal abscess associated with frontal bone osteomyelitis, resulting from trauma or frontal sinusitis. The classic clinical presentation consists of purulent rhinorrhea, fever, headache, and frontal swelling. The diagnosis is confirmed by CT scan and treatment requires intravenous antibiotics, analgesia, and surgical intervention. Early diagnosis and aggressive medical and surgical approach are essential for a good outcome. It rare and the early diagnosis is important; we describe the case of a 14-year-old adolescent with Pott’s puffy tumor who was initially treated inadequately, evolving with extensive frontoparietal abscess. The patient underwent surgical treatment with endoscopic endonasal and external approaches combined. Intravenous antibiotics were prescribed for a prolonged time, with good outcome and remission of the complaints.